A GIS-Based Analysis of Coastal Abrasion Risk Potential - Jamilah, Jamilah; Chaerul, Muhammad; Desi, Natsar; Erniati, Erniati; Harun, Muh. A. Yusuf; Dirman, Eris Nur (Newinera Publisher, 2025)
Coastal abrasion poses a significant threat to Indonesia, an archipelagic nation with one of the world’s longest coastlines. The phenomenon is particularly severe in Napabalano District, Muna Regency, where dense settlements, economic activities, and declining mangrove ecosystems increase exposure to erosion hazards. This study aims to assess the risk of coastal abrasion in Napabalano District using a GIS-based approach aligned with the Indonesian National Disaster Management Authority (BNPB) framework. Primary data, including GPS coordinates, satellite imagery, and field surveys, were integrated with secondary data such as demographic statistics, oceanographic parameters, and historical records of abrasion events. Spatial analysis in ArcGIS was employed to evaluate vulnerability, capacity, hazard, and disaster risk indices. Results show that all villages in Napabalano District fall into the high-risk category, with Napabalano and Napalakura recording the highest risk values due to concentrated populations, limited mangrove protection, and inadequate disaster management capacity. Social and economic vulnerabilities, including high poverty ratios and dependence on coastal livelihoods, exacerbate exposure, while institutional capacity remains critically low, marked by weak early warning systems and limited community preparedness. Mitigation strategies proposed include mangrove rehabilitation, strict coastal zoning enforcement, community-based disaster preparedness programs, and the establishment of effective early warning systems. These findings highlight the urgent need for integrated, multi-stakeholder approaches to strengthen resilience against coastal abrasion. The study provides a strategic basis for local government and community planning in managing and reducing the impacts of coastal hazards in Napabalano District.